Risk of banana Xanthomonas wilt spread through trade - Nakato, V.; Beed, Fenton D.; Ramathani, I.; Rwomushana, I.; Opio, F. (2013)
Banana Xanthomonas wilt is a systemic disease of banana plants. We investigated the risk of spreading Xanthomonas campestris pv. musacearum (Xcm) through asymptomatic mature bunches. Samples of banana fingers and rachis from markets within Kampala, Uganda and at border points of Uganda with DR Congo, Tanzania, Rwanda and Kenya were tested for the presence of Xcm through recovery of the bacterium onto semi-selective media. Fingers and rachis infected with Xcm were sampled weekly to determine survival duration in such materials. Characteristic colonies of Xcm were observed in 89 bunches. Within Kampala, various levels of Xcm were detected in the local markets at 21% from Kalerwe, 50% in Nakawa and Nakasera and 53% from Kasubi. At international borders, Xcm was detected at 17% in Malaba, 32% at Mutukula, 33% in Busia, 42% at Katuna/Kamwezi, 44% Mpondwe and 62% Mpanga. About 13% of the inoculated plants exhibited symptoms typical of Xcm infection. Xcm survived for up to six months, with colony counts of 25.3 cfu/gm, 23.1cfu/gm and 20.0 cfu/gm in the peel, pulp and rachis, respectively. This study demonstrated that Xcm is carried in traded banana materials over long distances and across borders. The pathogen can survive in the peel and rachis from markets up to 6 months and therefore these organs may act as sources of inocula for new infections. Consquently, there is need to improve on phytosanitary issues to manage spread of Xcm and spread of contamination to new areas.